Local Defence (Self-Defence) in Lithuania during the Nazi German Occupation (1941–1944) - Zizas, Rimantas (Genocidas ir rezistencija, 2001)
The article deals with the establishment and activities of local defence units (self-defence) that were to protect living sites and their residents; private and public property; various civil objects as well as to support anti-partisan operations. Right after the Germans had occupied Lithuania, self-defence functions were executed by armed security units, formed from the rebels of the June 1941 Uprising, former members of the Riflemen Union (earlier liquidated by the Soviets), enterprise workers and public servants. However, Germans, guided by their political interests and plans, with no prospects for Lithuania’s autonomy being included, dis- armed the units and otherwise hindered self-defence initiatives in general. Self-defence functions, in fact, were delegated to Lithuanian Police and Auxiliary Police reserve units, formed from loyal to the regime people, and strictly controlled by Germans. German authorities did not allow the organisation of armed defence structures on local basis, whereas the issue of unarmed ones was left to the Lithuanian self-government authorities and the initiative of local people. However, following the order of German administration, the so-called “night guard“ groups were formed in Eastern Lithuania and other areas with big concentration of “bandits“. Firearms being denied, the “night guards“ (some quite numerous) equipped themselves with sticks. Their duty was to carry surveillance, to detain suspicious persons, and to warn both police and people of possible danger. In fact, as far as the autumn of 1943, those “night guard“ groups were the only expression of self-defence organisations that had really existed. In summer 1943, first groups of “loyal“ residents were armed for operations against “banditry“. Besides, German and Lithuanian self-governing administrations negotiated, though unsuccessfully, the revival of the Riflemen Union. Finally in autumn 1943, consolidated Soviet underground activities provoked German authorities to allow the formation of armed self-defence bodies in Lithuania.